Applications of UV/Vis Spectroscopy in Characterization and Catalytic Activity of Noble Metal Nanoparticles Fabricated in Responsive Polymer Microgels: A Review. (2nd November 2018) - Begum, Robina; Farooqi, Zahoor H.; Naseem, Khalida; Ali, Faisal; Batool, Madeeha; Xiao, Jianliang; Irfan, Ahmad
ABSTRACT: Noble metal nanoparticles loaded smart polymer microgels have gained much attention due to fascinating combination of their properties in a single system. These hybrid systems have been extensively used in biomedicines, photonics, and catalysis. Hybrid microgels are characterized by using various techniques but UV/Vis spectroscopy is an easily available technique for characterization of noble metal nanoparticles loaded microgels. This technique is widely used for determination of size and shape of metal nanoparticles. The tuning of optical properties of noble metal nanoparticles under various stimuli can be studied using UV/Vis spectroscopic method. Time course UV/Vis spectroscopy can also be used to monitor the kinetics of swelling and deswelling of microgels and hybrid microgels. Growth of metal nanoparticles in polymeric network or growth of polymeric network around metal nanoparticle core can be studied by using UV/Vis spectroscopy. This technique can also be used for investigation of various applications of hybrid materials in catalysis, photonics, and sensing. This tutorial review describes the uses of UV/Vis spectroscopy in characterization and catalytic applications of responsive hybrid microgels with respect to recent research progress in this area. GRAPHICAL ABSTRACT: